THE SYSTEM APPROACH TO PROVIDING RESOURCES FOR REPAIR OF BRIDGES AND OVERBRIDGES IS USED - Pshinko, O. M.; Radkevich, A. V.; M'yaken'ka, I. V. (Science and Transport Progress, 2010)
The existing systems used for solving definite tasks, the system description of construction processes and the advent of a new branch – the construction systems engineering – have been analyzed in the article. The possibility of applying the system approach to providing resources for repair of bridges and overbridges has been investigated.